Molecular docking of hybrid coumarin thiazole derivative as anti-breast cancer on VEGFR-2 protein - Liswatini, Putri; Rahma, Sophia; Mariska, Putri; Anggraeni, Fibria; Agustin, Desti; Sari, Desi Puspita; Afrian, Mahisa Shzara; Auli, Winni Nur; Saputro, Anjar Hermadi (Pharmacy Reports, 2024)
VEGFR-2 is a tyrosine kinase receptor located on cell membranes, originally identified in endothelial cells but also expressed in tumor cells and various cancer types, including breast cancer. In breast cancer, VEGFR-2 expression is upregulated during early stages of primary tumors and invasive metastases, with elevated levels associated with lymph node metastasis and reduced survival outcomes. This computational study evaluated the potential of coumarin-thiazole derivative compounds against VEGFR-2 as anticancer agents using molecular docking analysis. Three coumarin-thiazole hybrid compounds (42a, 54a, and 54b) were assessed for their binding affinity to VEGFR-2, with sorafenib serving as the reference drug. The docking analysis utilized the three-dimensional structure of VEGFR-2 (PDB ID: 2OH4) downloaded from the RCSB Protein Data Bank. Ligand structures were prepared using molecular modeling software and converted to appropriate formats for analysis. Molecular docking was performed using AutoDockTools v.1.5.7, and protein-ligand interactions were visualized using BIOVIA Discovery Studio 2024 software.Method validation using the native GIG ligand yielded a binding energy of -10.88 kcal/mol. The binding energy values for the three test compounds were -9.81 kcal/mol for compound 42a, -12.71 kcal/mol for compound 54a, and -12.77 kcal/mol for compound 54b. Compound 54b demonstrated the strongest binding affinity to VEGFR-2, surpassing the native ligand GIG, the reference drug sorafenib, and the other test compounds. These results indicate that compound 54b represents the most promising candidate for anti-breast cancer therapy through VEGFR-2 targeting, warranting further experimental validation.